2012
DOI: 10.1016/j.jcmg.2012.03.007
|View full text |Cite|
|
Sign up to set email alerts
|

Low Quality and Lack of Clarity of Current Informed Consent Forms in Cardiology

Abstract: Guidelines on informed consent for clinical practice exhort physicians to use standard plain language to enhance patient comprehension and facilitate shared decision making. The aim of this study was to assess and improve quality and readability of current informed consent forms used in cardiology. We evaluated the currently used informed consent forms, previously written in Italian and English, of 7 common imaging examinations, according to the recommendations of scientific societies. For each text, we also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…Beginning in the 1980s, Conroy and Mulcahy [12] reported a high grade level (14.3, via Fry) of 28 pamphlets available to cardiac patients at a referral center in Ireland. More recently, Terranova et al [13] demonstrated a significantly higher than recommended RGL of patient consent forms utilized at a tertiary care referral center for 7 commonly performed examinations among cardiac patients, ranging from stress echocardiography to percutaneous coronary intervention. In addition, Mueller et al [14] demonstrated that the “Dear Patient” cardiovascular implantable device advisory letters offered by the Heart Rhythm Society significantly exceeded both the NIH-recommended and national mean RGLs.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in the 1980s, Conroy and Mulcahy [12] reported a high grade level (14.3, via Fry) of 28 pamphlets available to cardiac patients at a referral center in Ireland. More recently, Terranova et al [13] demonstrated a significantly higher than recommended RGL of patient consent forms utilized at a tertiary care referral center for 7 commonly performed examinations among cardiac patients, ranging from stress echocardiography to percutaneous coronary intervention. In addition, Mueller et al [14] demonstrated that the “Dear Patient” cardiovascular implantable device advisory letters offered by the Heart Rhythm Society significantly exceeded both the NIH-recommended and national mean RGLs.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and Gould for their interest in our paper (1). The "factually incorrect" doses reported in Figure 3 are indeed correct.…”
Section: R E P L Ymentioning
confidence: 78%
“…Ater the examinaion, the actual dose delivered should be stored in the paient's and laboratory's records. This simple process will gently force the doctor to learn what he/she should already know, enabling him/her to make more responsible choices 25 .…”
Section: The Order Of Magnitude and Risksmentioning
confidence: 99%